PENGARUH VOLUME PERDAGANGAN TERHADAP VOLATILITAS (Studi pada Bursa Efek Indonesia dan New York Stock Exchange) - Supriati, Putu Ayu; Wiagustini, Ni Luh Putu (E-Jurnal Manajemen, 2019)
The aims of this study is to determine the effect of stock trading volume on volatility, and to find out the differences of test results in two different markets. This research was conducted in the Indonesia Stock Exchange and in the New York Stock Exchange by selecting the Composite Stock Price Index (CSPI), which in each market as a sample in 2013 until 2018. The analysis technique used in this study, namely linear regression and different test two means. The results of this study indicate that stock trading volume has a significant positive effect on stock volatility, and market participants can take decisions based on stock volatility. The effect of the trading volume on volatility indicates that the higher the volume of stock trading will take the higher of the volatility. The test which was conducted in the two markets, confirm that the volatility in both markets, in addition, volatility on the Indonesia Stock Exchange is higher than the volatility of the New York Stock Exchange. The results of this study also confirm about the differences in the percentage of the effect of trading volume on volatility in both markets. Keywords : stock trading volume, volatility, Indonesia Stock Exchange, New York Stock Exchange